Feeding behavior of goats, castrated and uncastrated, supplemented with Vitamin E - Silva, Igor Cassiano Saraiva; Cutrim Junior, José Antônio Alves; da Silva, Edneide Marques; Pereira, Anderson Lopes; Mesquita, Saulo Antônio Araújo; Gomes, Ravana Sousa (Comunicata Scientiae, 2019)
The objective of this study was to evaluate the ethological and feeding behavior of male goats under the influence of climatic conditions, castration and supplementation with Vitamin E. The responses were analyzed by a behavior test factorial design with 2 x 2 (not spayed or neutered animal, the presence or absence of supplementation with Vitamin E), with 6 replicates. The time of feed intake, rumination, other activities, entertainment, salt intake frequency, water, urination and defecation were evaluated. The factors did not have any effect on the animal’s condition, or the vitamin supplementation (P>0.05) on rumination, other activities, defecation frequency and water consumption. Vitamin E intake had no effect on food and entertainment (P>0.05). There was a significant condition of the animal (P<0.05) on the salt intake and urination, for uncastrated animals without Vitamin E. Periods of the day (P<0.05) affected feed intake in all treatments. There was a significant difference (P<0.05) for rumination time. Vitamin E had little influence on ethological behavior, and castration is directly linked to the behavioral parameters of goats.